Dose-Dependent Influences of Ethanol on Ischemic Stroke: Role of Inflammation - Xu, Guodong; Li, Chun; Parsiola, Anne L.; Li, Jiyu; McCarter, Kimberly D.; Shi, Runhua; Mayhan, William G.; Sun, Hong (Frontiers in Cellular Neuroscience, 2019)
Chronic ethanol consumption dose-dependently affects both incidence and prognosis of ischemic stroke. Our goal was to determine whether the influence of chronic ethanol consumption on ischemic stroke is related to an altered inflammatory profile in the brain. Male C57BL/6J mice were divided into 6 groups and gavage fed with 0.175, 0.35, 0.7, 1.4, 2.8 g/kg/d ethanol or volume-matched water once a day for 8 weeks. Adhesion molecules, microglial activation, neutrophil infiltration, pro- and anti-inflammatory cytokines/chemokines, blood-brain barrier (BBB) permeability, and matrix metallopeptidases (MMPs) in the cerebral cortex before and following a 90-minute unilateral middle cerebral artery occlusion (MCAO)/24-hour reperfusion were evaluated. Brain ischemia/reperfusion (I/R) injury was significantly reduced in 0.7 g/kg/d ethanol group (peak blood ethanol concentration: 9 mM) and worsened in 2.8 g/kg/d ethanol group (peak blood ethanol concentration: 37 mM). Baseline E-selectin was downregulated in all ethanol groups, whereas baseline intercellular adhesion molecule-1 (ICAM-1) was only downregulated in 0.35 and 0.7 g/kg/d ethanol groups. Interestingly, baseline vascular cell adhesion molecule-1 (VCAM-1) was upregulated in 0.35, 0.7, and 1.4 g/kg/d ethanol groups. Post-ischemic upregulation of ICAM-1 and E-selectin were suppressed in all ethanol groups. Post-ischemic neutrophil infiltration and microglial activation were significantly less in the low-moderate (0.175-1.4 g/kg/day) ethanol groups but greater in the 2.8 g/kg/d ethanol group compared to the vehicle group. At basal conditions, ethanol increased one pro- and two anti-inflammatory cytokines/chemokines at the 0.7 g/kg/d dose, and thirteen pro and eight anti-inflammatory cytokines/chemokines at the 2.8 g/kg/d dose. After ischemia, 0.7 g/kg/day ethanol suppressed post-ischemic pro-inflammatory cytokines/chemokines and enhanced post-ischemic anti-inflammatory cytokines/chemokines. Moreover, 0.7 g/kg/day ethanol significantly reduced baseline MMP-9 activity and alleviated post-ischemic BBB breakdown. On the other hand, 2.8 g/kg/day ethanol worsened post-ischemic BBB breakdown. Our findings suggest that low-moderate ethanol consumption may prevent ischemic stroke and reduce brain I/R injury by suppressing inflammation, whereas heavy alcohol consumption may induce ischemic stroke and worsen brain I/R injury by aggravating inflammation.